Predictors of left ventricular dysfunction in hypertrophic cardiomyopathy: results from a nationwide registry. (3rd October 2022) - Brandao, M; Goncalves Almeida, J; Fonseca, P; Faria, R; Sousa, O; Fonseca, C; Fontes-Carvalho, R
Abstract: Introduction: Progression of hypertrophic cardiomyopathy (HCM) with incident left ventricular (LV) dysfunction (HCM-LVSD) is associated with poor prognosis and advanced heart failure (HF). Prevalence ranges from 5–10% in previous studies. Identification of predictors of adverse remodeling may improve risk stratification and prognostication in HCM. Purpose: To identify predictors of HCM-LVSD in a nationwide cohort of HCM patients (pts). Methods: Retrospective study including all HCM pts enrolled in a European country-based nationwide registry. HCM-LVSD group included pts with LV ejection fraction (LVEF) ≤50% at baseline and pts who developed LV dysfunction/dilated phenotype during follow-up. Multivariate logistic regression was performed to identify predictors of HCM-LVSD. Results: 1042 HCM patients (57.8% male, mean age at diagnosis 52 years) were included, of whom 81 (8%) belonged to the HCM-LVSD group. HCM-LVSD pts were mostly male (60.5%) and tended to be older at the time of diagnosis than those without LVSD (55 vs 52 years, p=0.054). HCM-LVSD pts were more often symptomatic at the index visit (84.1% vs 65.2%, p<0.001), with more functional impairment (New York Heart Association class III–IV: 18.5% vs 9.2%, p=0.021). Atrial fibrillation (21.3% vs 8.6%, p<0.001) and intraventricular conduction disturbances (28.6% vs 14.4%, p=0.002) were more prevalent in HCM-LVSD pts. HCM-LVSD pts had higher baseline left atrium (LA) volumes (52 vs 39 ml, p=0.001), lower LVEF (50 vs 67%, p<0.001) and higher rates of mitral regurgitation (79.0% vs 65.1%, p=0.011). Prevalence of obstructive HCM was lower in the HCM-LSVD group (25.3% vs 40.9%, p=0.007). Presence of late gadolinium enhancement (92.6% vs 74.6%, p=0.035) was more common in pts with LVSD. Baseline N-terminal pro–B-type natriuretic peptide was higher in HCM-LVSD (3839 vs 1281 pg/ml, p=0.027). There were no differences in the number and type of genetic variants between groups. In HCM-LVSD pts, implantation of cardioverter-defibrillators for secondary prevention was more frequent (28.6% vs 6.4%, p=0.002), as was the use of pacemaker (16.7% vs 7.0%, p=0.002). During a mean follow-up of 5.3±6.1 years, hospitalization for HF (50.0% vs 11.3%) and all-cause mortality (12.3% vs 2.9%, p<0.001) were more frequent in HCM-LVSD group. After multivariate analysis, higher LA volume (odds ratio [OR] 1.03, 95% confidence interval [CI] 1.01–1.05, p=0.003) and nonobstructive HCM (OR 2.74, 95% CI 1.03–7.27, p=0.043) were independent predictors of HCM-LVSD. Conclusions: In this large nationwide cohort of HCM pts, prevalence of LVSD was 8%, in line with existing literature. In this cohort, larger LA volumes and nonobstructive HCM predicted progression to HCM-LVSD. Funding Acknowledgement: Type of funding sources: None.